2017
DOI: 10.1055/s-0036-1597972
|View full text |Cite
|
Sign up to set email alerts
|

Late-term Effects of Surgery on Nasal Functions in Patients who Underwent Total Laryngectomy Surgery

Abstract: Introduction  There is a common opinion that losing airway functions in total laryngectomy patients cause changes in nasal physiological rates. Studies conducted to review the subject present gaps, especially in terms of objective measurements. Objective  We evaluated late-term effects of surgery on nasal functions in patients who underwent total laryngectomy surgery more than two years ago. Methods  We included in the study 22 patients who had undergone total laryngectomy, as well as 24 healthy subjects wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Karaoglu D et al conducted a study in which they studied the long-term effects of laryngectomy on nasal functions and found that mean mucociliary clearance time for laryngectomized patients was 1017.14 seconds whereas in control group it was 662.5 seconds suggesting that physiological alteration in the nose due to bypass of nasal airway, leads to reduced ciliary clearance and impaired olfaction which can affect patients quality of life and safety. [8] In our study, mean nasal mucociliary clearance time (NMCT) was 934.97±75.9 seconds, these results were similar to study done by El-Sharnouby et al who conducted a study on 31 patients and found that the mean saccharine test time recorded 2 months following tracheostomy was 732.6± 323.4 seconds and at 6 months postoperatively was 1615±1042 seconds and was statistically significant. [9] However, study done by Yadav SP et al on 30 tracheostomized patients showed nasal mucociliary clearance time of 444±22.8 seconds when saccharin test was done at 3 weeks following tracheostomy and NMCT further reduced to 371.4±32.4 seconds in patients who were tracheostomized for more than 3 weeks, suggesting that, following tracheostomy, there is a significant decrease in nasal mucociliary clearance time, particularly after 3 weeks postoperatively.…”
Section: Discussionsupporting
confidence: 90%
“…Karaoglu D et al conducted a study in which they studied the long-term effects of laryngectomy on nasal functions and found that mean mucociliary clearance time for laryngectomized patients was 1017.14 seconds whereas in control group it was 662.5 seconds suggesting that physiological alteration in the nose due to bypass of nasal airway, leads to reduced ciliary clearance and impaired olfaction which can affect patients quality of life and safety. [8] In our study, mean nasal mucociliary clearance time (NMCT) was 934.97±75.9 seconds, these results were similar to study done by El-Sharnouby et al who conducted a study on 31 patients and found that the mean saccharine test time recorded 2 months following tracheostomy was 732.6± 323.4 seconds and at 6 months postoperatively was 1615±1042 seconds and was statistically significant. [9] However, study done by Yadav SP et al on 30 tracheostomized patients showed nasal mucociliary clearance time of 444±22.8 seconds when saccharin test was done at 3 weeks following tracheostomy and NMCT further reduced to 371.4±32.4 seconds in patients who were tracheostomized for more than 3 weeks, suggesting that, following tracheostomy, there is a significant decrease in nasal mucociliary clearance time, particularly after 3 weeks postoperatively.…”
Section: Discussionsupporting
confidence: 90%
“…Several literature reports have described in detail the significant alterations in the physiology and histology of the nasal mucosa following complete resection of the larynx. 4,5 Our report describes two cases of postlaryngectomy sinonasal cancer and points to the potential coexistence of more than one carcinogenetic mechanism for this tumor constellation.…”
Section: Introductionmentioning
confidence: 79%
“…Our study cases led to the reasonable line of thought that another factor could also play a role in the pathogenesis of the disease in laryngectomized patents. Regarding altered physiology, several studies have pointed out the increase in endonasal temperature and moisture, the disappearance of the nasal cycle, as well as the decrease in endonasal blood flow and mucociliary activity following laryngectomy. Histologically, the loss of nasal function leads to atrophic rhinitis with destruction of the goblet cells and cilia, myxoid degeneration, fibrosis, neovascularization, and squamous metaplasia .…”
Section: Discussionmentioning
confidence: 99%
“…It is also indicated in literature that the prevalence of enteric gram negative bacillus increases in the tracheobronchial tree in those with long term tracheostomy [18]. In addition, Li et al reported that the presence of tracheostomy poses an independent risk factor for Acinetobacter development [19]. It is suggested that the patients are taken in bronchial hygiene training programs for protection against severe lung infections by way of repressing the mucus [20,21].…”
Section: Resultsmentioning
confidence: 99%